2022
DOI: 10.3390/jcm11113226
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Insertion Site of Nexplanon: Description of a Case Report and Systematic Review of the Literature

Abstract: The etonogestrel (ENG) implant is among the most effective reversible contraceptives. It can be a good option for patients with different chronic diseases due to no clinically significant effects on lipid metabolism or liver function. Some limitations in the use of this type of device are represented by social and psychiatric disorders, where the easy accessibility of the device becomes a negative feature. In these patients several cases of self-removal or damage to the device have been reported. We report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We previously reported that MHT increases the risk of migraine in postmenopausal women ( 10 ), indicating that the same hormonal factors that cause an interruption in the normal menstruation cycle may also increase the risk of migraine. Various routes of MHT, such as transdermal patches and etonogestrel implants, have been recently implemented ( 36 , 37 ). A previous study reported that the transdermal patch might improve menstrual migraine ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that MHT increases the risk of migraine in postmenopausal women ( 10 ), indicating that the same hormonal factors that cause an interruption in the normal menstruation cycle may also increase the risk of migraine. Various routes of MHT, such as transdermal patches and etonogestrel implants, have been recently implemented ( 36 , 37 ). A previous study reported that the transdermal patch might improve menstrual migraine ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Daily combined pills or transdermal estrogens associated with oral progesterone can easily be prescribed [ 20 ]. Etonogestrel implant [ 21 ] is interesting in case of chronic diseases and social disorders only in case of proper ovarian function, but should not be prescribed in case of estrogens deficiency. Psychological support remains mandatory in all cases of POI.…”
Section: Discussionmentioning
confidence: 99%
“…implant [21] is interesting in case of chronic diseases and social disorders only in case of proper ovarian function, but should not be prescribed in case of estrogens deficiency. Psychological support remains mandatory in all cases of POI.…”
Section: Plos Onementioning
confidence: 99%
“… 11 Furthermore, the existence of alternative insertion sites had been found to be useful to patients with psychiatric disorders and low compliance, hence the implanon is an effective and safe contraceptive device, not easily accessible by the user. 12 …”
Section: Discussionmentioning
confidence: 99%